Perbandingan Waktu Erupsi Gigi Susu Incisivus Pertama Pada Bayi Usia Yang Diberi Susu Asi Dan Yang Diberi Susu Fomula - Ratih Variani (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2018)
Background: Exclusive breastfeeding coverage in East Nusa Tenggara was 42,8% according to Riskesdas 2013. Most mothers gave formula feeding or partial to their babies accounting for 57,2%. Nutrition is one of the factors that correlate with tooth eruption. A baby gains nutrition through breastfeeding or formula. Formula feeding has low nutrition compared with breastfeeding. Aims: Knowing the eruption comparison of primary central incisors of babies with breastfeeding compared with formula. Method: Observational research was applied to gain the information needs. The samples were divided into two groups: the first group had breastfeeding while the second group with formula. Each group accounted for 30 babies. The research locations were Posyandu of Pasir Panjang and Oebobo’s public health center. Data were analyzed by using Man Whitney test. Results: Average tooth eruptions of babies with breastfeeding and formula accounting for 7 months and 9 months, consecutively. Babies with breastfeeding had primary central incisors eruption two months earlier compared with babies with formula. Man Whitney statistic analyzed indicated there is no significant difference in tooth eruption between babies with breastfeeding and formula. Conclusion: Eruption of Primary central incisors in babies with breastfeeding compare with formula is the same.